The effect of contextual teaching and learning model with ethnomathematics approach on students’ conceptual understanding and critical thinking - Ari Purwa Kusuma; Nurina Kurniiasari Rahmawati (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: Mathematics learning demands not only conceptual understanding but also critical thinking skills. However, studies in Indonesian classrooms have shown that students often struggle with both abilities. A possible cause is the use of teacher-centered approaches that do not facilitate student engagement or meaningful learning experiences.Aim: This study aims to investigate the effect of the Contextual Teaching and Learning (CTL) model integrated with an ethnomathematics approach on students’ conceptual understanding and critical thinking skills in mathematics.Method: This research employed a quantitative approach with a quasi-experimental design. The sample consisted of 60 ninth-grade students from two different classes selected using simple random sampling. Data were collected through validated test instruments and analyzed using Multivariate Analysis of Variance (MANOVA) with a significance level of 0.05.Results: The findings showed that both the conceptual understanding and critical thinking skills of students in the experimental group improved significantly compared to the control group. The MANOVA results indicated a significance value of 0.000 (< 0.05), confirming a significant effect of the CTL model with ethnomathematics on both dependent variables. The average N-Gain score in the experimental class was higher (0.68) than in the control class (0.62).Conclusion: The implementation of the CTL model with an ethnomathematics approach has a positive and significant effect on improving students’ conceptual understanding and critical thinking in mathematics. This approach enables students to relate mathematical content to cultural contexts, making learning more meaningful and engaging.